Analisis pengaruh perang dagang AS-China bagi kondisi ekonomi ASEAN-4 periode 2017-2020 - Jarwo, Reja Ale; Purnomo, Didit (Journal of Economics Research and Policy Studies, 2024)
International trade is the exchange of goods and services between citizens of two or more countries by mutual agreement. However, the increasingly intensive trade can trigger conflicts during trade, which are called trade wars. The current trade war between the United States and China is playing with each other's trade tariffs. This research analyzed the influence of the US-China Trade Balance, ASEAN balance of payments, and imports related to ASEAN-4 economic conditions. This observation selects secondary data from the World Bank, International Monetary Fund (IMF), and CEIC Data. The data used in this research is panel data on 4 ASEAN countries, including Indonesia, Malaysia, Vietnam, and Thailand, in 2017-2020. Meanwhile, the analysis technique uses the Common Effect Model (CEM) approach. The final calculation results show that the US-China trade balance and import variables influenced ASEAN-4 economic conditions in 2017-2020.